PSYCHOLOGY OF TERRORISM: BRIEF NOTES (Journal of the Spanish Institute for Strategic Studies, 2018)
terrorism is a global problem. no country in the world can consideritself free of the scourge of fear and terror. geopolitical, strategic, economic,or social interests agitate the world map giving rise to confl ictsamong countries or among regions. in recent years, some jihadist terroristgroups or organizations have emerged and, with strong militarypower and uncommon violence, are causing panic, suff ering, poverty,and desolation among the population in many countries. with studiedmedia politics and defending a specifi c ideology, terrorist groupsof diff erent political and religious persuasion, and a strong personalityamong its members, were able to obtain the following of young fanatics.many of these young fanatics were socially rootless, their conductbeing subject to permanent psycho-sociological analyses. a terrorist’sviolent behavior is not a mental condition per se, but rather a consequenceof a process of socialization that aff ects the mind and the behavior.a terrorist is not a psychopath, and the psychological sequels thatthe terror these groups cause the victims and the population that suff ershas a long persistence in most cases.